2016
DOI: 10.1002/2015jg003113
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of remotely sensed litterfall in tropical and subtropical forests of Taiwan

Abstract: Litterfall is important for returning nutrients and carbon to the forest floor, and microbes decompose the litterfall to release CO 2 into the atmosphere. Litterfall is a pivotal component in the forest biogeochemical cycle, which is sensitive to climate variability and plant physiology. In this study, we combined field litterfall estimates and time series (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) climate (the Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
2
16
0
1
Order By: Relevance
“…Litterfall is an important pathway for the return of organic matter (OM) and nutrients from above-ground biomass (AGB) to the forest floor, which is directly linked to the soil C pool (Wang et al, 2016). Soil organic carbon depends on the quantity of litterfall and the rate of its decomposition (Oelbermann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Litterfall is an important pathway for the return of organic matter (OM) and nutrients from above-ground biomass (AGB) to the forest floor, which is directly linked to the soil C pool (Wang et al, 2016). Soil organic carbon depends on the quantity of litterfall and the rate of its decomposition (Oelbermann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies reported that litter mass production synchronizes with canopy processes linked to phenology, vegetative, and reproductive growth phases and biomass production (Zeilhofer et al, 2012). The quantification of the litter production at higher temporal and spatial scales is cumbersome and restricts the development of the linkage between litter crop and complex canopy processes (Wang et al, 2016). Based on the existing literature, climatic variables (temperature and precipitation) and stand characteristics (vegetation type, canopy density, age, site quality, climate, and phenology) are some of the important elements that influence litterfall (Qin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one review study reported that the litterfall mass of a boreal forest was on the low end, whereas that of a tropical forest was on the high end (Bray and Gorham 1964). Many studies have demonstrated that on a local scale litterfall in forest ecosystems is dependent on forest type, species composition, forest age, soil fertility, and disturbances (Bray and Gorham 1964;Liu et al 2004;Wang et al 2016;Lin et al 2017;Feng et al 2019). A disturbance, which refers to a temporary change in environmental conditions, may have the most profound effects on the amount and pattern of litterfall because of the changes caused to the ecological and physiological processes of the forest (Lodge et al 1991;Lin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter redistribution is likely to be a major driver of belowground responses to canopy disturbance associated with storm events (Lodge, Cantrell, & Gonz alez, 2014;Sanford et al, 1991;Silver, Hall, & Gonz alez, 2014;Turton, 2008;Vargas, 2012). High velocity winds result in a large deposition of biomass from the canopy to the forest floor (Frangi & Lugo, 1991;Horng, Yu, & Ma, 1995;Lin, Hamburg, Tang, Hsia, & Lin, 2003;Lodge, Scatena, Asbury, & Sanchez, 1991;Wang, Lin, & Huang, 2016;Whigham, Olmsted, Cano, & Harmon, 1991;Xu, Hirata, & Shibata, 2004). The contribution of green leaves and live branches to total litterfall during these disturbances results in a pulse of C and nutrients to the soil (Gonz alez, Lodge, Richardson, & Richardson, 2014;Lin, Chang, Wang, & Liu, 2002;Lodge, McDowell, & McSwiney, 1994;Lodge et al, 1991;Silver et al, 2014;Sullivan, Bowden, & McDowell, 1999).…”
Section: Introductionmentioning
confidence: 99%